Grain boundary plane rotation analysis for FCC bicrystal structures using MD simulation - Ryoichi Chiba; Panya Kansuwan (International Journal of Computational Materials Science and Engineering, 2021)
Grain boundary (GB) plane rotation, one of the GB engineering mechanisms, was investigated using the activation–relaxation technique by molecular dynamics simulation. The simulation systems considered in this work are bicrystals with Lennard-Jones-type interatomic potential. The systems of four GB types established are symmetric (SYM), asymmetric (ASYM), symmetric zigzag (SZ), and high-angle zigzag (HZ) models. Of the first two models, [Formula: see text]5 (310) for SYM and [Formula: see text] tilted for ASYM particularly provided reference atomic potential energy distributions and structures at minimum energy state at 0 K. The characteristic of SYM is the discrete atomistic potential distributions which are distinct from ASYM. The other two models based on zigzag-like GBs were created by rotating GB planes about [001] at the center of a [Formula: see text]5 (310)[Formula: see text]GB system for the SZ case and a high-angle GB system for the HZ case. Simulation results show that the initially tilted GBs kinetically transferred to relaxed states for shorter-length GBs through a series of curved GBs. The GBs consist of different combinations of order defect segments, amorphous regions, and defect-free regions. A mechanism proposed is the GB plane rotation, the rate of which is structure-dependent. A low-[Formula: see text] coincidence site lattice boundary section can stabilize the systems at a specified metastable state.
Keywords: Metal Forming Simulation Techniques; Metallurgy and Material Forming; Microstructure and mechanical properties